2020
DOI: 10.1177/1535370220928933
|View full text |Cite
|
Sign up to set email alerts
|

Neferine induces mitochondrial dysfunction to exert anti-proliferative and anti-invasive activities on retinoblastoma

Abstract: Retinoblastoma is common primary intraocular malignancy of infants and childhood. Neferine is a major bisbenzylisoquinoline alkaloid derived from the lotus plumule in Nelumbo nucifera. This study evaluated the mitigation role of Neferine on retinoblastoma in vitro and in vivo. Xenotransplantation model was established by injecting WERI-Rb-1 cells subcutaneously. Upon induction of retinoblastoma , mice were intraperitoneally injected with Neferine (0, 0.5, 1, 2 mg/kg) or ethanol every 3 days for 30 days. Tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…There is at least one report of the N. nucifera alkaloid neferine on retinoblastoma, a common primary intraocular childhood and infant malignancy. Wang et al [100] observed that neferine inhibited the proliferation and viability of the WERI-Rb-1 human retinoblastoma cell line associated with reduced protein expression of Ki-67 and Survivin. Neferine treatment reduced microtubule-like structure formation, the number of nodes/high power field, and VEGF protein levels, demonstrating its anti-invasive capability.…”
Section: Eye Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…There is at least one report of the N. nucifera alkaloid neferine on retinoblastoma, a common primary intraocular childhood and infant malignancy. Wang et al [100] observed that neferine inhibited the proliferation and viability of the WERI-Rb-1 human retinoblastoma cell line associated with reduced protein expression of Ki-67 and Survivin. Neferine treatment reduced microtubule-like structure formation, the number of nodes/high power field, and VEGF protein levels, demonstrating its anti-invasive capability.…”
Section: Eye Cancermentioning
confidence: 99%
“…In addition to the in vitro study, Wang et al [100] investigated the anticancer effects of neferine using an in vivo retinoblastoma model. WERI-Rb-1 cells were subcutaneously injected in female athymic nude mice, and the tumor-bearing animals were treated with 0.5-2 mg/kg of neferine every 3 days for 30 days.…”
Section: Eye Cancermentioning
confidence: 99%
“…Lotus plumule contains neferine, a bisbenzylisoquinoline alkaloid shown to have anti-cancer properties in past years [64,65]. Neferine suppressed the development of CML cell lines of K562 [66].…”
Section: Lotus Plumulementioning
confidence: 99%
“…Neferine (2 µM) effectively reduces angiogenesis, while inhibiting tumor development and invasion in WERI‐Rb‐1 retinoblastoma cells. Furthermore, neferine treatment inWERI‐Rb‐1 cells showed downregulation of nuclear protein Ki67 and vascular endothelial growth factor expression and facilitating apoptosis (Wang et al., 2020). Neferine (5 µM) prevents proliferative vitreoretinopathy in in vitro model of retinal pigment epithelial cells by inhibiting epidermal growth factor‐mediated cell division through cell cycle arrest at gap 1 phase (G1 phase) and epithelial mesenchymal transition (EMT) by increased expression of p21 and p27.…”
Section: Pharmacological Properties Of Neferinementioning
confidence: 99%
“…Neferine (10% & 20%) reduces the blood glucose and increased serum insulin levels with decreased lipid peroxidation and increased activities of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and GST in streptozotocin‐induced diabetic rats. The underlying molecular mechanism of wound healing activity of neferine was attributed through downregulation of inflammatory genes such as NF‐κβ, TNF‐α, IL‐6, and IL‐1β and activation of Nrf‐2 pathway (Wang et al., 2020). In myoblast L6 cells, neferine (50–150 μM) induced the expression of glucose transporter type 4 (GLUT4) thereby preventing insulin resistance.…”
Section: Pharmacological Properties Of Neferinementioning
confidence: 99%